A novel simulation for the design of a low cycle fatigue experimental testing programme. (1st January 2017) - Beesley, Ross; Chen, Haofeng; Hughes, Martin
Highlights: Proposal of an innovative concept for the design of an experimental testing programme. Novel method for low cycle fatigue (LCF) life assessment. Method applied to a new bespoke industrial test specimen. Demonstrates capabilities of the method for an industrial, experimental application. Abstract: This paper proposes an innovative concept for the design of an experimental testing programme suitable for causing Low Cycle Fatigue crack initiation in a bespoke complex notched specimen. This technique is referred to as the Reversed Plasticity Domain Method and utilises a novel combination of the Linear Matching Method and the Bree Interaction diagram. This is the first time these techniques have been combined in this way for the calculation of the design loads of industrial components. This investigation displays the capabilities of this technique for an industrial application and demonstrates its key advantages for the design of an experimental testing programme for a highly complex test specimen.